2021
DOI: 10.1016/j.colsurfb.2021.112063
|View full text |Cite
|
Sign up to set email alerts
|

Injectable niclosamide nanohybrid as an anti-SARS-CoV-2 strategy

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 69 publications
(68 reference statements)
1
2
0
Order By: Relevance
“…Identical absorption bands were also obtained from the as-made NIC-MgO-HPMC, which demonstrated the formation of broken π-π stacking interactions [38]. The greatest challenge in NIC delivery is its low aqueous solubility as previously reported by many researchers, including our group by repurposing technology using polymers [39,40] as well as inorganic clays [41].…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Identical absorption bands were also obtained from the as-made NIC-MgO-HPMC, which demonstrated the formation of broken π-π stacking interactions [38]. The greatest challenge in NIC delivery is its low aqueous solubility as previously reported by many researchers, including our group by repurposing technology using polymers [39,40] as well as inorganic clays [41].…”
Section: Resultssupporting
confidence: 65%
“…The greatest challenge in NIC delivery is its low aqueous solubility as previously reported by many researchers, including our group by repurposing technology using polymers [39, 40] as well as inorganic clays [41].…”
Section: Resultsmentioning
confidence: 99%
“…Newly, it has been identified that reusing already available medications could be a good method to formulate an efficient drug for SARS-CoV-2 infection. Though there are many FDA-accepted medications, it has been shown that the anthelmintic medication niclosamide (NIC) has remarkably great capability versus COVID-19 [ 132 ]. Sanoj Rejinold et al used a simple self-assembling method in which Zein NPs were effectively utilized to load NICs.…”
Section: Nanoparticles As a Great Blessingmentioning
confidence: 99%